Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper highlights that the authorities in the Republic of Korea recognize the pension policy challenges ahead, and a first wave of reforms has already been launched. Despite the reforms to date, much remains to be done. Without further reforms, the public pension systems in Korea are not financially sustainable. This paper considers options for moving to a funded first-pillar pension system. The main results show that a sustainable, funded pension system can be achieved in Korea with reasonably modest changes to key parameters and extra financing.